Soil weathering analysis using a portable X-ray fluorescence (PXRF) spectrometer in an Inceptisol from the Brazilian Cerrado - Silva, Sérgio Henrique Godinho; Hartemink, Alfred E.; Teixeira, Anita Fernanda dos Santos; Inda, Alberto Vasconcellos; Guilherme, Luiz Roberto Guimarães; Curi, Nilton (Applied clay science, 2018)
Portable X-ray fluorescence (pXRF) spectrometers allow rapid detection of soil elements and owing to several advantages have been increasingly used in many environmental samples, soils included. This study aimed to: i) evaluate the potential of pXRF for soil profile characterization; ii) use pXRF for investigating soil weathering through elemental contents quantification in sand, silt, and clay fractions; and iii) spatially evaluate elemental composition in the soil profile to assess variation within and between horizons. An Inceptisol from the Brazilian Cerrado was morphologically described and composite samples from the A, B, C, and Cr horizons were collected for physical/chemical characterization. Additional samples were collected from a regular grid (12.5 × 12.5 cm, n = 24) in the soil profile for further analyses with pXRF in the air-dried fine earth (<2 mm), as well as in the sand, silt, and clay fractions, which were also mineralogically characterized by X-ray diffractometry (XRD). Contents of Ca, K, Al, Si, Zn, and Cu decreased with depth. Calcium, K, Ba, Cr, and Rb contents were less abundant in the sand fraction of the Cr horizon, when compared to the A horizon, whereas Si increased from the Cr to A horizon, probably due to the relative residual accumulation of quartz in this fraction in the A horizon, which was supported by XRD analyses. There was a considerable variation of elemental concentrations with depth and within horizons. Elemental composition obtained by pXRF can help in soil genesis studies indicating weathering pathways and is a powerful tool for complementing XRD data. Future studies can evaluate correlations between soil properties and contents of elements that are now easily obtained by pXRF, such as V, Sr, Rb, and Ba. •First time mineralogy of sand, silt and clay fractions of soil was related to pXRF.•pXRF results have high correspondence to soil mineralogy.•Mineral weathering pathways can be followed with pXRF analysis.•Spatializing elemental contents indicates variability among and within soil horizons.•Rb, V, Ba, Sr can be easily obtained by pXRF and correlated to soil weathering.